2022
DOI: 10.3390/su141912803
|View full text |Cite
|
Sign up to set email alerts
|

On the Study of the Sustainable Development of Intangible Cultural Heritage of Indigenous Peoples’ Diets—Take the Protection of Geographical Indications as an Example

Abstract: From the perspective of geographical indications, this article introduces the methods used by the geographical indication system to protect indigenous peoples’ diets as an intangible part of their cultural heritage. By collecting and analyzing the data of the five major intellectual property offices of the world, we can understand the protection status of the intangible cultural heritage of indigenous peoples’ diets. Difficulties and controversies in the protection of food-related intangible cultural heritage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“… Community participation The inheritance of ICH should be based on community participation and joint efforts, rather than solely being completed by the government or professional institutions [ 31 ]. Inheritance method Its inheritance should be diversified and can be completed through oral tradition, practice, experience, performance, education, and other ways [ 32 ]. Readability Its inheritance should be understood and recognized, and should not be too complex or profound, making it difficult for the public to accept and understand [ 33 ].…”
Section: Research Modelmentioning
confidence: 99%
“… Community participation The inheritance of ICH should be based on community participation and joint efforts, rather than solely being completed by the government or professional institutions [ 31 ]. Inheritance method Its inheritance should be diversified and can be completed through oral tradition, practice, experience, performance, education, and other ways [ 32 ]. Readability Its inheritance should be understood and recognized, and should not be too complex or profound, making it difficult for the public to accept and understand [ 33 ].…”
Section: Research Modelmentioning
confidence: 99%
“…Studies that examine geographical indications and sustainable gastronomy together academically have become widespread in recent years. Thanks to geographical indications, gastronomic products become visible and attract attention [25]; it becomes easier to preserve the local culinary culture and transfer it to future generations [26]; local production and consumer demand increase [27]; environmental, social, and economic sustainability is achieved [28]; institutionalization of products [29] and legal support become easier [30]. Therefore, in light of these research studies, we evaluate that examining the geographically indicated Tokat Sucuk in Turkish cuisine culture within the scope of sustainable gastronomy will contribute to the relevant literature.…”
Section: Sustainable Gastronomy and Geographical Indicationmentioning
confidence: 99%
“…Finally, the construction of cultural ecological environment requires the participation and promotion of the whole society. The government needs to strengthen the protection and support for NRM, various industries need to actively inherit and develop NRM culture, and the public needs to actively understand and support the inheritance and development of NRM culture [19][20].…”
Section: Cultural Ecology Constructionmentioning
confidence: 99%